Microstructure studies of strontium titanate thin films prepared by so-gel dip-coating method - Maarof, Saleha (Universiti Teknologi Malaysia, 2013)
Strontium titanate (SrTiO3) thin films were deposited on corning glass by using dip coating method. Strontium nitrate, titanium (IV) isopropoxite, ethylene glycol and nitric acid have been use to prepared sol-gel of strontium titanate. Structural and its surface morphologies of the films were characterize by using X-ray Diffraction (XRD) and Atomic Force Microscopy (AFM), respectively. It have been determine that the films were strontium nitrate compound for as-prepared sample with lattice parameter; a = b = c = 0.78 nm and strontium titanate compound for annealing at 500 °C temperature with lattice parameter 0.39 nm. The films annealed at 500 °C showed the films were polycrystalline with orientation; (110), (111), (200) and (211). The grain sizes were in the range of 17.4 to 60.7 nm and surface roughness in range 22.9 to 70.1 nm.